Evaluation of compressive strength of eco-friendly cementitious composites incorporating waste oyster shells under sodium chloride solution exposure - Jinwoong Kim; Inyeong Cha; Byungkyu Jo; Heeyoung Lee (Case Studies in Construction Materials)
The development of the marine industry and the continuous increase in oyster production have caused the accumulation of large quantities of waste oyster shells, with only a small portion being recycled. Unrecycled waste oyster shells cause environmental problems, produce odors, and harm marine ecosystems. Simultaneously, aggregates such as sand are in high demand in the construction industry. Waste oyster shells, primarily comprising calcium carbonate (CaCO₃), have similar material characteristics to sand and can be used as a sand substitute. In this study, oyster shell cementitious composites were produced to assess the potential of waste oyster shells as a sand replacement. The experimental parameters included the use of admixtures, curing in either fresh water or sodium chloride solution, and various curing durations. The specimens were cured for 91 days in fresh water and 30, 60, or 91 days in sodium chloride solution. Nine oyster shell cementitious composite specimens measuring 50 mm × 50 mm × 50 mm were fabricated for each experimental condition, resulting in a total of 144 specimens. When cured in sodium chloride solution, the compressive strength decreased as the curing time increased, while the compressive strengths cured in fresh water and sodium chloride solution for 91 days were 38.8 and 34.55 MPa, respectively. Thus, the specimens cured in sodium chloride solution retained more than 80 % of the strength of those cured in fresh water. Therefore, waste oyster shells can serve as an eco-friendly construction material and are a viable alternative to sand.